Penyebab Rendahnya Pelaporan Insiden Keselamatan Pasien Di Fasilitas Kesehatan Primer Provinsi Maluku - Manuhutu, Feby (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Methods: This article is a quantitative recearch with descriptive correlation method and using cross-sectional design. The sample in this study amounted to 37 health centers located in Maluku Province, specifically in Central Maluku district and West Seram district, using cluster random sampling technique. Data were analyzed using the chi-square test. Objective: The purpose of the study was to analyze the causes of under reporting of patient safety incidents in Primary Health Facilities in Maluku Province Results: The results of this study showed that of the 37 respondents, the majority of respondents with Psychological Factors: Perception is Good as many as 24 respondents (64.9%), the majority of Psychological Factors: Attitude is Positive as many as 20 respondents (54.1%), the majority of Psychological Factors: Motivation is low as many as 22 respondents (59.5%), the majority of Leadership Organizational Factors are High as many as 23 respondents (62.1%), and the majority of respondents did not report IKP as many as 21 respondents (56.8%). Conclusion: Underreporting of patient safety incidents in primary health facilities in Maluku province was caused by psychological factors: perception (0.001); attitude (0.000); and motivation (0.015), and organizational factors: leadership (0.027), as evidenced by p values <0.05. Suggestion: The role of primary health facilities leaders is needed, in the form of structured training to improve reporting, as well as paying attention to perceptions, attitudes, and increasing external motivation, so that patient safety incident reporting as an effort to improve the quality of health services can be achieved.